Moderna's Vaccine Using the K-Nearest Neighbor (KNN) Method: An Analysis of Community Sentiment on Twitter - Marlyna Infryanty Hutapea; Arina Prima Silalahi (Jurnal Penelitian Pendidikan IPA, 2023)
The COVID-19 is still in Indonesia. The government has made efforts to stop the COVID-19 virus, by moving vaccination program. There are various types of vaccines, one of which is moderna vaccine or MRNA-1273 that applied intramuscularly. The vaccination programs using modern vaccines creates different opinions in public, especially among Twitter users. The opinion uploaded will be the data on Public Sentiment Analysis on Twitter About Moderna Vaccines Using K-Nearest Neighbor Method research. In this study, TF-IDF method is used for weighting the words and KNN for classifying the sentiment into two groups of sentiments, namely positive and negative. The tools used in this research are Rapid miner to collect tweet data and Python for sentiment classification and evaluation. From the test results Based on 50 training data when k = 3 it is known that the accuracy value is 80%, precision is 80%, recall is 100% and F-Measure is 89%.